Pelatihan Manajemen Data Kependudukan dengan Ms. Excel di Desa Gedangan Kecamatan Sidayu Gresik - Fenny Fitriani; Gangga Anuraga; Artanti Indrasetianingsih (JAST : Jurnal Aplikasi Sains dan Teknologi, 2020)
Making a voter list is an initial process to support the implementation of regional head elections. Making this voter list was carried out by village officials using population data stored in Ms. Excel. Until now, this process was done manually by sorting age data using the Excel sort function. By carrying out this process, village officials still have to carry out a separate sorting of population data less than 17 years old who have been married. Apart from these data, the data that must be separated by village officials is data on residents over 17 years of age who have died. With these processes, village officials need more time to be able to create voter lists. One of the village officials who carry out the process is the village apparatus in Gedangan Village, Sidayu, Gresik. For solving this problem, training was conducted for ten Gedangan village officials in data management using Ms. Excel. The training materials provided were consolidating the use of sort and filter data, using forms in filling in data and using pivot tables. The method used in this training is to use interactive discussion. The training was held at the village hall in Gedangan Village, Sidayu, Gresik. With this training, village officials could more easily determine the list of voters who met the requirements.